2019
DOI: 10.1371/journal.pone.0217768
|View full text |Cite
|
Sign up to set email alerts
|

An observational, prospective, multicenter study on rescue high-frequency oscillatory ventilation in neonates failing with conventional ventilation

Abstract: Background To achieve gas exchange goals and mitigate lung injury, infants who fail with conventional ventilation (CV) are generally switched to high-frequency oscillatory ventilation (HFOV). Although preferred in many neonatal intensive care units (NICUs), research on this type of rescue HFOV has not been reported recently. Methods An online registry database for a multicenter, prospective study was set to evaluate factors affecting the response of newborn infants to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…A recent prospective observational multi-center study on rescue HFOV in neonates failing conventional ventilation reported that rescue HFOV was successful in improving gas exchange in 58% of subjects. 19 Although demographic and treatment characteristics at baseline were similar between groups, subjects who died had lower birthweight (1,655 6 1,091 vs 1,858 6 1,027 g, P ¼ .004), higher initial F IO 2 (0.83 vs 0.72, P < .001), and higher rate of exposure to inhaled nitric oxide (22% vs 11%, P ¼ .004) compared with survivors. Moreover, survivors demonstrated a mean reduction in oxygenation index after 1 h of HFOV, whereas nonsurvivors did not improve.…”
Section: Discussionmentioning
confidence: 87%
“…A recent prospective observational multi-center study on rescue HFOV in neonates failing conventional ventilation reported that rescue HFOV was successful in improving gas exchange in 58% of subjects. 19 Although demographic and treatment characteristics at baseline were similar between groups, subjects who died had lower birthweight (1,655 6 1,091 vs 1,858 6 1,027 g, P ¼ .004), higher initial F IO 2 (0.83 vs 0.72, P < .001), and higher rate of exposure to inhaled nitric oxide (22% vs 11%, P ¼ .004) compared with survivors. Moreover, survivors demonstrated a mean reduction in oxygenation index after 1 h of HFOV, whereas nonsurvivors did not improve.…”
Section: Discussionmentioning
confidence: 87%
“…Limited data about rescue use of HFOV in premature infants with severe respiratory failure can be found in the literature because it is di cult to de ne the "rescue" use of HFOV and conduct a randomized control trial [9,20,23,24]. Therefore, most studies have focused on comparisons between elective HFOV versus conventional ventilation [14][15][16]18].…”
Section: Discussionmentioning
confidence: 99%
“…Severe refractory respiratory failure was de ned when patients with a PaO 2 /FiO 2 ratio under 150 on two consecutive arterial blood gas (ABG) samples and/or had an initial oxygenation index (OI) ≥ 20 [21]. Poor response to conventional ventilation was de ned as failure to decrease PCO 2 > 10% and/or FiO 2 > 20% after 1 hour treatment by conventional ventilation (CV) at maximal settings [22,23]. Exclusion criteria were patients < 24 weeks of gestation, incomplete medical records, and patients with severe congenital anomalies (ex.…”
Section: Study Design Settings and Patientsmentioning
confidence: 99%
“…The Rescue-HFOV Trial Group prospectively evaluated factors affecting the response of 372 subjects who underwent rescue HFOV after failing conventional ventilation. 85 Subjects were separated into 2 groups: survivors and nonsurvivors or those who received extracorporeal membrane oxygenation (n ¼ 8). All subjects initially underwent volume-controlled ventilation with V T < 7 mL/kg and were managed with a permissive hypercapnia strategy to maintain a pH > 7.25.…”
Section: High-frequency Ventilationmentioning
confidence: 99%